Elastomers: From Theory to Applications - Heinrich, Gert; Lang, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Elastomers: From Theory to Applications" focuses on the current state of the art of elastomers, both in modern developments of rubber-like compositions and applications and from a theoretical perspective. The series of 13 publications offer the latest results in several specific sub-areas of elastomer research or review selected fields and concepts. Of particular interest are new structures and functionalities incorporated into elastomers, leading to the enhanced properties of crosslinked elastomeric materials for several applications, and/or to a better understanding of the structure‒property relationships and practical behaviour.